Pengaruh Audit Fee, Opini Audit Going Concern, Ukuran Perusahaan, Pergantian Manajemen dan Kepemilikan Publik Terhadap Auditor Switching - Ertina Nur’ Anisa; Yunita Christy (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
ABSTRACT This study is to analyze the effect of audit fees, going-concern audit opinion, company size, management change, and public ownership on auditor switching both partially and simultaneously. Sample of this study are manufacturing company that has been listed on Indonesia Stock Exchange (BEI) for period 2015-2017. The data analysis technique used is logistic regression. Partial test results show that public ownership influences the auditor switching. While the audit fee, going-concern audit opinion, company size, and management change have no effect on auditor switching. Simultaneous test results indicate that the audit fee, going-concern audit opinion, company size, management change, and public ownership are able to explain the occurrence of auditor switching in manufacturing companies listed on Indonesia Stock Exchange in 2015-2017 by seven percent and the remaining ninety three percent explained by other variables outside the research model. Keywords: Auditor switching, Audit fee, going concern audit opinion, company size, management turnover, public ownership